2014
DOI: 10.1080/14786435.2014.984006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of phonon-mediated thermal transport in a Ni50Al50melt: case analysis of the influence of the process on the kinetics of solidification

Abstract: The phonon-mediated contribution to the thermal transport properties of liquid NiAl alloy is investigated in detail over a wide temperature range. The calculations are performed in the framework of equilibrium molecular dynamics making use of the Green-Kubo formalism and one of the most reliable embedded-atom method potentials for the intermetallic alloy. The phononmediated contribution to the thermal conductivity of the liquid alloy is calculated at equilibrium as well as for the steady state. The relative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Finally, our result for the NiAl potential in Ref. [16] is in fair agreement with previous results for thermal conductivity using the same potential [17].…”
Section: Results and Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our result for the NiAl potential in Ref. [16] is in fair agreement with previous results for thermal conductivity using the same potential [17].…”
Section: Results and Analysissupporting
confidence: 91%
“…[17] (where it was found that, in our units, L cc = 0.035 A −1 ps −1 , L qq = 0.930 eV 2Å−1 ps −1 , and L cq = −0.020 eVÅ −1 ps −1 ) with our values obtained using the same potential, it seems that our values for L cc and L qq are in agreement, while we find a value for L cq significantly larger in magnitude than the value found in Ref. [17]. This seems to account for the difference in values for Q * c between this work and Ref [9].…”
Section: Results and Analysismentioning
confidence: 99%
“…Another conceptual approach for generation accurate and self-consistent databases of the transport and thermodynamic properties of liquid alloys can be based on molecular dynamics (MD) simulations [13][14][15][16][17][18][19][20][21][22][23]. This approach is completely free of the limitations inherent for experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed [19][20][21]23] a theoretical framework for calculation of the mass and heat transport coefficients in a binary liquid alloy via equilibrium MD simulation in conjunction with the Green-Kubo formalism using the fluxes independent of reference frame. Furthermore, we have compared our results on mass and heat transport in a Ni 50 Al 50 melt obtained with two state-of-the-art EAM potentials [26,27] developed for the alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation